Behavior classification of Japanese black bear (Ursus thibetanus japonicus) by using a GPS telemetry system with activity sensor - Nakagawa, K. (Kyoto Univ. (Japan)); Hasegawa, H; Tamatani, H; Takayanagi, A (Forest Research, Kyoto - Kyoto University (Japan), 2002)
A Global Positioning System (GPS) collar with activity sensor was deployed on a Japanese black bear (Ursus thibetanus japonicus) in early winter of 2001, and the collar was programmed to fix every 30 minutes for seven days. The behavior pattern of the black bear can be classified into "rest", "stay", and "move" by the obtained moving distance and the activity rate. Three patterns, set at interval 60, 120, and 180 minutes, were simulated, and the behavior classification estimated from each fix interval data was compared with the data of 30 minutes interval. The "rest", of which consecutive time was long, showed high concordance rate, while the "stay" and the "move", were short, showed low concordance rate as fix interval was long. Since the accuracy of behavior classification was determined by the relationship between consecutive time of behavior and fix interval, fix interval should be programmed with due consideration of consecutive time of the behavior according to the research subject.